(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
The main aim of is to assessment of the socio-economic development level of rural and urban – rural communities in Middle Pomerania compared to communities of neighboring voivodeships. The differentiation and the level of socio-economic development level was determined using the synthetic indicator based on the characteristics of demography, technical and social infrastructure, entrepreneurship and labor market and local finance. The analysis covered 409 rural and urban – rural communities. The data come from the Local Data Bank of the Central Statistical Office in 1999 and 2014 years. Middle Pomerania is characterized by a similar level of socio-economic development for the Zachodniopomorskie voivodeshipand little lower than the Pomorskie and Wielkopolskie voivodeship. The level of changes between 1999 and 2014 is similar to Pomorskie and Wielkopolskie, and higher than in Zachodniopomorskie voivodeship.